The female brain [videorecording (DVD)] - Cummings, Whitney, 1982-; Cummings, Whitney, 1982-; Vergara, Sofía, 1972-; Kebbell, Toby; Marsden, James, 1973-; Punch, Lucy, 1977-; Seymour, Jane, 1951-; Feldstein, Beanie; Strong, Cecily, 1984-; Brizendine, Louann, 1952- (Shout Factory, 2018)
No-nonsense neuroscientist Julia is researching the biochemistry of the female brain of three couples: newlyweds Zoe and Greg, whose career troubles seep into their relationship; Lisa and Steven, who are looking to spice up their stuck-in-a-rut marriage; and Lexi who can't help trying to change her boyfriend Adam. Meanwhile, the straight-laced Julia's own synapses start to fire when a handsome new subject joins her study.